Feed Restriction Modulates the Fecal Microbiota Composition, Nutrient Retention, and Feed Efficiency in Chickens Divergent in Residual Feed Intake - Siegerstetter, Sina-Catherine; Petri, Renée M.; Magowan, Elizabeth; Lawlor, Peadar G.; Zebeli, Qendrim; O'Connell, Niamh E.; Metzler-Zebeli, Barbara U. (Frontiers in Microbiology, 2018)
There is a great interest to understand the impact of the gut microbiota on host's nutrient use and FE in chicken production. Both chicken’s feed intake and gut bacterial microbiota differ between high and low-feed efficient chickens. To evaluate the impact of the feed intake level on the feed efficiency (FE)-associated variation in the chicken intestinal microbiota, differently feed efficient chickens need to eat the same amount of feed, which can be achieved by feeding chickens restrictively. Therefore, we investigated the effect of restrictive versus ad libitum feeding on the fecal microbiome at 16 and 29 days posthatch (dph), FE and nutrient retention in chickens of low and high residual feed intake (RFI; metric for FE). Restrictively fed chickens were provided the same amount of feed which corresponded to 85% of the ad libitum fed group from 9 dph. FE was determined for the period between 9 and 30 dph and feces for nutrient retention were collected on 31 to 32 dph. From the 112 chickens (n = 56 fed ad libitum, and n = 56 fed restrictively), 14 low RFI and 15 high RFI ad libitum fed chickens, and 14 low RFI (n = 7 per sex) and 14 high RFI restrictively fed chickens were selected as the extremes in RFI and were retrospectively chosen for data analysis. Bray-Curtis dissimilarity matrices showed significant separation between time points, and feeding level groups at 29 dph for the fecal bacterial communities. Relevance networking indicated positive associations between Acinetobacter and feed intake at 16 dph, whereas at 29 dph Escherichia/Shigella and Turicibacter positively and Lactobacillus negatively correlated to chicken’s feed intake. Enterobacteriaceae was indicative for low RFI at 16 dph, whereas Acinetobacter was linked to high RFI across time points. However, restrictive feeding-associated changes in the fecal microbiota were not similar in low and high RFI chickens, which may have been related to the higher nutrient retention and thus lower fecal nutrient availability in restrictively fed high RFI chickens. This may also explain the decreased RFI value in restrictively fed high RFI chickens indicating improved FE, with a stronger effect in females.